Hiring people with criminal records in South Carolina: examining businesses’ hiring practices and views on incentives - Martin, Tara E. (Criminal justice policy review, 2020)
The stigma of a criminal history has well-documented adverse effects on the efforts of ex-offenders to secure employment. What is less well understood is whether interventions or educational efforts targeting employers would improve access to the labor market for this population. We report results from two surveys to better understand attitudes toward hiring ex-offenders among samples of South Carolina businesses. Our results suggest that about half of employers routinely conduct background checks and approximately 60% would consider hiring someone with a criminal record. A key additional focus of our study was whether businesses were aware of various programs and incentives to encourage the hiring of ex-offenders. Our results suggest relatively low levels of awareness among the surveyed businesses and provide limited support for the idea that awareness is linked to more favorable attitudes toward hiring ex-offenders. We conclude with an assessment of study limitations and directions for future research.